Socioeconomic mechanisms of myopia boom in China: a nationwide cross-sectional study. Issue 6 (16th June 2021) - Ma, Yingyan; Lin, Senlin; Li, Liping; Jia, Yingnan; Zou, Haidong
Abstract : Objectives: To assess the association between socioeconomic development and the myopia boom in China. Design: Nationwide cross-sectional study. Setting: We used data from the China Family Panel Study (CFPS 2010), and the Chinese National Survey on Students' Constitution and Health (CNSSCH 2010). Participants: Participants included 33 600 individuals and 14 226 families from the CFPS 2010, and 86 199 students aged 7–12 years from the CNSSCH 2010. Measures: The main measure was students' visual impairment (defined as Snellen visual acuity ≤20/25 (0.8) in the worse eye) rate of each province (or municipality or autonomous region); other measures included the Gini coefficient of property, logarithm of average property, Gini coefficient of education, average education duration and return-to-education rate of each province (or municipality or autonomous region). The visual impairment rate was calculated using students' data, aged 7–12 years, from the CNSSCH 2010. The Gini coefficient of property and logarithm of average property were calculated using the families' data from the CFPS 2010; the Gini coefficient of education, average education duration and return-to-education rate were calculated using individuals' data aged 18–44 years from the CFPS 2010. Results: The urban environment (coefficient: 0.209; p<0.001), Gini coefficient of property (coefficient: 1.979; p=0.005), logarithm of average property (coefficient: 0.114; p<0.001), average education duration (coefficient: 0.041; p<0.001) and return-to-education rate (coefficient: 0.195; p<0.001) were positively associated with the logit function of visual impairment rate. Conclusions: Economic development may promote an increased desire to pursue wealth. Regarding high return to education and a fairly competitive education system, individuals are likely to pursue wealth through education, which is associated with a heavier education burden and higher prevalence rates of myopia.